Pendekatan Health Belief Model (HBM) Untuk Menganalisis Kepatuhan Pasien Diabetes Mellitus Dalam Menggunakan Insulin Di Kota Banjarmasin - Aulia Damayanti; Anabaena Chicade; Halimatus Sadiyah; Kerin Petrisia; Lalu T. R. Elwin; M. Yericho; Maulida Putri Andini; Muhammad Rezky Rachman; Muhammad Yuzhar; Pebrianti` Pebrianti; Putri Olivia Nayaken; W.P.P Dewi Ratna; Shinta Kumala Dewi; Sita Razni Imani; Umi Hasanah; Yenni Al Zahra; Erlina Syamsyu (Jurnal Pelayanan Kefarmasian dan Sains, 2022)
Diabetes mellitus is a group of metabolic diseases characterized by chronic hyperglycemia due to defects in insulin secretion, insulin action, or both. In terms of the prevalence of DM patients 2.86% in Banjarmasin City (Rikesdas, 2018). Currently insulin is the most effective therapy for DM patients, but patients tend to refuse to give insulin by injection. Health Belief Model (HBM) is a model of individual health beliefs in determining attitudes to take or not to take action on health behavior.Objective: To see the relationship between the Health Belief Model (HBM) approach and 5 main concepts to analyze the compliance of diabetes mellitus patients in using insulin in the people of Banjarmasin City.Method: Descriptive by testing hypotheses and obtaining answers to a question, the data can be collected through questionnaires or questionnaires.Results: Based on the characteristics of the patient's adherence to insulin, it showed 62.5% often, 25.0% sometimes, 3.1% rarely used insulin and 9.4% did not use it. There is a perceived susceptibility to not taking insulin, with the highest number indicating an increase in blood sugar. the perceived severity of the individual's belief in the severity of the disease he suffers, the perceived benefits have a significant positive relationship to patient compliance in using insulin. There is a significant relationship between patient compliance in using insulin and perceived barriers.Conclusion: Susceptibility, severity, benefit, and perceived self-confidence have a significant positive effect on patient adherence to insulin use. Meanwhile, based on medication adherence of diabetes mellitus patients in using insulin, it was not significantly affected by the perceived barriers.